Studies on secondary scintillation from xenon admixtures with helium - Fernandes, Andreia Filipa de Moura (2021)
PhD thesis in Physics Engineering, in the field of Instrumentation, performed under scientific guidance of Doutora Cristina Maria Bernardes Monteiro and Doutor Carlos Alberto de Oliveira Henriques, presented to the Physics Department of the Faculty of Sciences and Technology of the University of Coimbra.